Archiwalia władz i administracji miasta Bydgoszczy w zasobie Archiwum Państwowego w Bydgoszczy (Kronika Bydgoska, 2010)
The history of Bydgoszcz is very popular among researchers. The municipal archives of Bydgoszcz are the basie source materiał for research on the city’s history and the present. The preserved archives document resolution-passing, executive rights, as well as administrative and judicial rights of offices and organs of the municipal self-govemment, their tasks in the scope of admin- istrative, economic, social and cultural development of the city. The files of the authorities and the administration of Bydgoszcz are presented chrono- logically, describing their source contents. The files of Bydgoszcz city from the years 1559-1945, in total 58,500 archival units, are the largest group of archives. The Municipal National Council in Bydgoszcz has only 46 archival units from the years 1945-1950. Much better preserved are the files of the Municipal Management Board in Bydgoszcz -1,284 units. Eąually numerous are the files of the Presidium of the Municipal National Council in Bydgoszcz -1,477 units. The files of the municipal administration organs functioning in the years 1973-1990, i.e.the Municipal National Council in Bydgoszcz numbers only 326 units, and the files of the Municipal Management Board in Bydgoszcz -only 2 units. In spite of the diverse State of preservation, the archival heritage of the functioning of the municipal authorities remains the source of the first-rate importance for research on the city’s history.